The impact of public debt on state borrowing cost in the US bond market before the great recession. Issue 3 (3rd September 2018) - Charles, Cleopatra; Shon, Jongmin
Abstract : Purpose: The purpose of this paper is to use data on municipal bond sales in the US primary market for the period 1984–2007 to explore the effect of debt levels on the cost of borrowing for state governments. Design/methodology/approach: This paper employs OLS and two-stage least squares regression model using instrumental variables. Findings: The empirical analysis finds that despite the steady increase of state debt in recent years, there is no evidence that the market penalizes states with high-debt levels relative to other states. Originality/value: The findings urge states to exercise prudence when making borrowing decisions because high-debt levels have the potential to crowd out spending for essential services and can lead to budget imbalances in the long term.